CALCULATION OF THE PARAMETERS FOR ATMOSPHERICMODEL FOR THE EARTH - Y, Waleed I; B, Yasser C; A, Mohammed N (Al-Nahrain Journal of Science, 2018)
In this model we have used the balance forces theory for a vertical column of air for calculate the pressure equation, also calculate the variations of density, pressure, temperature and molecular weight with altitude from sea level up to 700 km. The equations parameters are derived analytically using the hydrostatic equation. In addition, the equations of the gravitational acceleration, speed of sound and scale height are derived. Equation of temperature and equation of molecular weight merged in single equation is called equation of molecular temperature. Results of these equationshave been from solving by using computer. Finally these results are discussed, which represent the variation of atmospheric parameters with altitude. We can use this model for study effect of earth’s atmosphere on airplanes and moving bodies inside it.